Anisotropic fracture forming limit diagram considering non-directionality of the equi-biaxial fracture strain. (15th October 2018) - Park, Namsu; Huh, Hoon; Yoon, Jeong Whan
Abstract: This paper is concerned with modeling of anisotropic fracture forming limit diagram considering non- directionality of the equi- biaxial fracture strain. A new anisotropic ductile fracture criterion is developed based on the Lou–Huh ductile fracture criterion (Lou et al., 2012). In an attempt to predict the forming severity of advanced high- strength steel (AHSS) sheets, the proposed fracture criterion is converted into a Fracture Forming Limit Diagram (FFLD) and anisotropic fracture locus considering the sheet metal orientation. Tensile tests of the DP980 steel sheet with the thickness of 1.2 mm are conducted using various specimen geometries including pure shear, dog- bone, and flat grooved specimens. With Digital Image Correlation (DIC) method, equivalent plastic strain distribution on the specimen surface is computed until surface crack initiates. The fracture predictability of the proposed fracture criterion is evaluated with the experimental results which cover a wide range of stress states in various loading directions. By comparing fracture strains obtained from the experiments with the ones predicted from the proposed fracture criterion, it is clearly confirmed that the fracture criterion proposed is capable of predicting the equivalent plastic strain at the onset of fracture with great accuracy over a wide range of stress states while keeping non-directionality of the equi- biaxial fracture strain.